Air pollution in relation to very short-term risk of ST-segment elevation myocardial infarction: Case-crossover analysis of SWEDEHEART. (15th January 2019) - Sahlén, Anders; Ljungman, Petter; Erlinge, David; Chan, Mark Y.; Yap, Jonathan; Hausenloy, Derek J.; Yeo, Khung Keong; Jernberg, Tomas
Abstract: Objective: Studies have related air pollution to myocardial infarction (MI) events over days or weeks, with few data on very short-term risks. We studied risk of ST-segment elevation MI (STEMI) within hours of exposure to air pollution while adjusting for weather. Methods: We performed a case-crossover study of STEMI cases in Stockholm, Sweden (Jan 2000–June 2014) based on SWEDEHEART. Exposures during hazard periods up to 24 h prior to admission were compared to bidirectionally sampled control periods. Risks attributable to sulphur dioxide (SO2 ), nitrogen dioxide (NO2 ), ozone and particulate pollutants (PM2.5, PM10 ) were studied in conditional logistic regression models for interquartile range increments. Results: Risk of STEMI (n = 14, 601) was associated with NO2 (strongest at 15-h lag) and with PM2.5 (strongest at 20-h lag), in single-pollutant models adjusting for air temperature and humidity (NO2 : odds ratio (OR; 95% confidence interval) 1.065 (1.031–1.101); PM2.5 : 1.026 (1.001–1.054)). After adjusting models for atmospheric pressure (significantly associated with STEMI risk at 14–24-h lags), NO2 remained highly statistically significant (1.057 (1.022–1.094)) but not PM2.5 (1.024 (0.997–1.052)). No associations were seen for SO2, ozone or PM10 . Conclusion: Risk of STEMI rises within hours of exposure to air pollutants, with strongest impact of NO2 . These findings are complementary to earlier reports which have not acknowledged widely the importance of very short-term fluctuations in air pollution. Highlights: Risk of STEMI rises within hours of exposure to air pollutants. Strongest association was seen for NO2 at a 15-h lag. Weaker association was noted for PM2.5 at a 20-h lag.